2021
DOI: 10.2147/ijn.s320278
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Damaged Renal Epithelial Cells After Repair by Porphyra yezoensis Polysaccharides with Different Sulfation Degree on the Calcium Oxalate Crystal–Cell Interaction

Abstract: Background The interaction between urinary microcrystals and renal epithelial cells is closely related to kidney stone formation. However, the mechanism of cell state changes that affect crystal–cell interaction remains unclear. Methods This study investigated the relationship between the sulfate group (–OSO 3 − ) content in Porphyra yezoensis polysaccharide (PYP) and the ability to repair damaged cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Injury to renal tubular epithelial cells is considered to be an important cause of the formation of renal stones [ 39 ]. Changes in cell-membrane structure and adhesion sites for stone crystals happened in damaged cells [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Injury to renal tubular epithelial cells is considered to be an important cause of the formation of renal stones [ 39 ]. Changes in cell-membrane structure and adhesion sites for stone crystals happened in damaged cells [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis is an active transport process that consumes energy. Cells in good condition have high metabolism and sufficient energy and are more likely to endocytose crystals adhering to the cell surface and reduce the harm of adhering crystals to cells (Sun et al, 2021; Taguchi et al, 2021). Taguchi et al (Borjigin et al, 2023) demonstrated that a fatty acid–binding protein promoted the development of renal CaOx stones by attenuating the phagocytosis of crystals by macrophages and renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…I G U R E 13 Schematic diagram of carboxymethylated desmodium styracifolium polysaccharide inhibited the adhesion of nanoCOD crystals to HK-2 cell membranes and promoted crystal endocytosis. and are more likely to endocytose crystals adhering to the cell surface and reduce the harm of adhering crystals to cells(Sun et al, 2021;Taguchi et al, 2021).Taguchi et al (Borjigin et al, 2023) demonstrated that a fatty acid-binding protein promoted the development of renal CaOx stones by attenuating the phagocytosis of crystals by macrophages and renal tubular cells. Furthermore, CDSPs promoted nanoCOD crystal endocytosis(Figures 11 and 12), inhibited the nanoCOD crystal-induced opening of mPTPs in HK-2 cells (Figure6), increased the mitochondrial membrane potential (Figure5), and promoted the cell cycle transition from the G2/M and S phases to the G1 phase (Figure2).…”
mentioning
confidence: 99%
“…Sulfated-modified polysaccharides are primarily used for antioxidant, antibacterial, antiviral, antitumor, anticoagulation, and immunomodulatory research [24][25][26]. However, less research has been conducted on their use in repairing damaged cells [27,28]. Previously, four sulfated U. pinnatifida polysaccharides (UPPs) were synthesized and their structures were characterized.…”
Section: Introductionmentioning
confidence: 99%